Enhanced bioavailability of Quercetin-loaded niosomal in situ gel for the management of Parkinson’s disease - Revankar, Abhishek A.; Patil, Archana S.; Karishetti, Reshma; Chougule, Krutuja R.; Patil, Priyanka; Salokhe, Abhijit (Frontiers in Pharmacology, 2025)
BackgroundParkinson’s disease (PD) is the second most prevalent neurological disorder, characterized by motor symptoms such as tremor and rigidity due to the degeneration of dopaminergic neurons in the substantia nigra. This study investigates the formulation of quercetin, a natural bioflavonoid with potent antioxidant and anti-inflammatory properties, as niosomes for intranasal delivery to enhance its bioavailability and therapeutic potential for PD.MethodsThe niosomal formulation was optimized for critical parameters including particle size, entrapment efficiency, and zeta potential. Male Wistar rats were utilized to assess the effects of quercetin-loaded niosomes on motor function, dopaminergic neuron protection, and oxidative stress alleviation.ResultsThe optimized niosomal formulation exhibited a particle size of 195 nm, a polydispersity index (PDI) of 0.29, a zeta potential (ZP) of −30.63 mV, and an entrapment efficiency (EE) of 82.77%. In vivo evaluations conducted using the haloperidol-induced PD model revealed significant enhancements in behavioural, biochemical, and histopathological outcomes when compared to both disease controls and the standard treatment group. Additionally, short-term stability tests confirmed the robustness of the formulation.ConclusionThe findings suggest that the quercetin-loaded niosomal formulation offers improved drug delivery and efficacy, indicating its potential as a superior treatment option for PD compared to conventional dosage forms. This approach may pave the way for enhanced therapeutic strategies targeting the neurodegenerative processes underlying Parkinson’s disease.